Commissure-based buccal mucosal flap - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Commissure-based buccal mucosal flaps extending to the retromolar trigone have been used for anterior intraoral mucosal defects. The flap was utilized successfully in 26 patients who had vermilion defect (14 cases), obliteration of the anterior gingivobuccal sulcus (8 cases), and anterior maxillary defect (4 cases).
Keywords: CLEFT-PALATE SURGERY; MUSCULOMUCOSAL FLAP; RECONSTRUCTION